Application of MFCA and dynamic programming in operations improvement: A case study - Atchara Songkham (2018)
© Springer-Verlag Berlin Heidelberg 2015. This study aimed to present an application of Material Flow Cost Accounting (MFCA) to discover loss in the process and dynamic programming in decision making of improvement solutions. The research focused on internal supply chain operations of the case study. Based on MFCA analysis, the overall cost can be classified as the cost of positive product as 46.97% and the cost of negative product as 53.03%. The highest cost of negative product was material cost (MC) 45.52% following by system cost (SC) 6.41%, and energy cost (EC) 1.10% of the total product cost. The improvement solutions were proposed for MC reduction. Industrial engineering problem solving tools; cause and effect diagram, pareto diagram and why-why analysis, were used to investigate root causes for negative MC. Seven improvement solutions were proposed and evaluated based on MFCA calculation. The decision making was carried out using dynamic programming when the incursion was formulated using the cost of positive product increased by each solution. Finally, only the 1st, 2nd, 6th and 7th solution were selected and the cost of positive product can be increased from 46.97% to 56.08% and the cost of negative product reduced from 53.03% to 43.92%